Exposures to chemical contaminants: What can we learn from reproduction and development endpoints in the amphibian toxicology literature?. (May 2019) - Slaby, Sylvain; Marin, Matthieu; Marchand, Guillaume; Lemiere, Sébastien
Abstract: Environmental contamination is one of the major factors or cofactors affecting amphibian populations. Since 2000, the number of studies conducted in laboratory conditions to understand impacts of chemical exposures increased. They aimed to characterize biological effects on amphibians. This review proposes an overview of biological responses reported after exposures to metals, phytopharmaceuticals or emerging organic contaminants and focuses on endpoints relating to reproduction and development. Due to amphibian peculiar features, these periods of their life cycle are especially critical to pollutant exposures. Despite the large range of tested compounds, the same model species are often used as biological models and morphological alterations are the most studied observations. From the results, the laboratory-to-field extrapolation remained uneasy and exposure designs have to be more elaborated to be closer to environmental conditions. Few studies proposed such experimental approaches. Lastly, gametes, embryos and larvae constitute key stages of amphibian life cycle that can be harmed by exposures to freshwater pollutants. Specific efforts have to be intensified on the earliest stages and notably germ cells. Graphical abstract: Image 10502069 Highlights: Pollution is considered as one of the causes of amphibian decline. Lab studies have been mainly conducted to describe pollutant effects on amphibians. Exposure effects on gametes remained very understudied. Reproduction and development are key issues to address in amphibian toxicology. Abstract : Lab studies were mainly conducted to characterize pollutant effects on amphibians. Reproduction and development, affected by contaminant exposures, are key issues to address in amphibian toxicology.